Cortical Brain Functions – The Brodmann Legacy in the 21st Century - Damiani, Daniel; Nascimento, Anna Maria; Pereira, Leticia Kühl (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
In 1909, Korbinian Brodmann described 52 functional brain areas, 43 of them found in the human brain. More than a century later, his devoted functional map was incremented by Glasser et al in 2016, using functional nuclear magnetic resonance imaging techniques to propose the existence of 180 functional areas in each hemisphere, based on their cortical thickness, degree of myelination (cortical myelin content), neuronal interconnection, topographic organization, multitask answers, and assessment in their resting state. This opens a huge possibility, through functional neuroanatomy, to understand a little more about normal brain function and its functional impairment in the presence of a disease.
Keywords: Brodmann areas; brain cortical areas; intelligence circuitry; brain functions; new brain areas; learning circuitry